2000
DOI: 10.1007/s007050070072
|View full text |Cite
|
Sign up to set email alerts
|

Pityriasis rosea - a virus-induced skin disease? An update

Abstract: Pityriasis rosea (PR) is an acute, inflammatory skin disease of unknown cause. Clinical and experimental findings indicate an infectious etiology of PR. Various infectious agents including viruses have been proposed as causative agents and their presence in PR samples has been extensively investigated. Recently, human herpesvirus 7 was linked to PR, but contradictory findings have been reported by various investigators. Here, we describe the features of PR that suggest an infectious cause and review the data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
5

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 57 publications
1
28
0
5
Order By: Relevance
“…Repeated attempts [52,[63][64][65] to isolate a virus by inoculating lesional biopsy specimens, blood, pharyngeal and rectal swabs with various cell lines failed to confirm a cytopathic effect and failed to demonstrate viral antigens by immunofluorescence assays [66]. Two studies by electron microscopy [52,67] also reported absence of viral particles from lesional biopsy specimens of patients with PR.…”
Section: Evidence Against An Infectious Aetiologymentioning
confidence: 94%
“…Repeated attempts [52,[63][64][65] to isolate a virus by inoculating lesional biopsy specimens, blood, pharyngeal and rectal swabs with various cell lines failed to confirm a cytopathic effect and failed to demonstrate viral antigens by immunofluorescence assays [66]. Two studies by electron microscopy [52,67] also reported absence of viral particles from lesional biopsy specimens of patients with PR.…”
Section: Evidence Against An Infectious Aetiologymentioning
confidence: 94%
“…Clinical and experimental findings suggest the pathogenic role of an infectious agent (1,2). Viral and bacterial causes have been proposed, but convincing answers have not yet been found (3). A link between Borrelia burgdorferi and PR was suggested in the 1990s and a roseolar eruption has been reported as a clinical manifestation of the second stage of Lyme disease (LD) (4,5).…”
Section: Sirmentioning
confidence: 97%
“…Diese Beobachtung ließ sich spä-ter jedoch nicht mehr bestätigen. In keiner der Studien konnte im Verlauf ein Anstieg von HHV-7-IgM-und HHV-7-IgGAntikörpern beobachten werden, was bei einer akuten Infektion oder Reinfektion zu erwarten gewesen wäre [4].…”
Section: äTiologieunclassified